UJI PERFORMANCE TERHADAP PERUBAHAN OVERSIZE CYLINDER LINER PADA SEPEDA MOTOR 225 CC.pdf - Moch Rayhan Azward (2021)
The process of oversizing the piston is mostly done on motors that have exceeded the size tolerance limit between the piston and the cylinder liner. The oversized process is a replacement with a piston diameter larger than the previous size of 70 mm. the research object uses a 225cc motorbike. In this study, a calculation analysis will be carried out to determine the effect of motor performance with a piston diameter of 72 mm and 74 mm and the impact on fuel with an octane value of 92.The aim of the oversize process is to determine the effect of motor performance and to determine the impact of fuel consumption after it is done oversize process. The results show that by oversizing the piston, the stroke volume increases, but the pressure in the combustion chamber decreases, the compression ratio increases. As for power and force, it is relatively the same as a standard size motorbike, as well as a slight increase in fuel consumption.